IMPLEMENTATION OF THE ONE VILLAGE ONE BILLION POLICY IN THE MOROTAI ISLAND REGION FROM THE LOCAL GOVERNMENT PERSPECTIVE - Bakri La Suhu; Rahmat Suaib; Abdullah Kaunar; Saiful Paturo (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2026)
This research is in principle to analyze and explain the implementation and use of One Billion funds in Morotai Island Regency, which has been implemented well in accordance with the applicable provisions in accordance with Sambiki Village Regulation Number 02 of 2014 concerning the 2014 Village Revenue and Expenditure Budget which is guided by Government Regulation Number 60 of 2014 concerning Village Funds Sourced from the State Revenue and Expenditure Budget in Article 19, which explains that village funds are used to finance the implementation of government, development, community, and community empowerment, and are prioritized for community development and empowerment. Meanwhile, the obstacles experienced in the use of One Billion funds are (1) low human resources of Sambiki village government officials, (2) lack of experience of village government officials in using One Billion funds due to educational levels, (3) Lack of coordination from the Sub-district and Village Community Empowerment Agency (BPMD), and (4) lack of community participation in village development.